Comparison of Bactrocera Fruit Fly Captures Using Basil and Celery Leaf Extracts in Karang Bayan Plantation - Ratna Trimilia Kurnia; I Putu Artayasa; Mohammad Liwa Ilhamdi; M. Yamin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The objective of this study was to assess the ratio of fruit fly captures using attractants derived from basil and celery extracts, as well as to examine the impact of attractant concentrations in basil and celery leaf extracts on fruit fly catches. Traps made from recycled mineral water bottles were baited with basil and celery extracts containing essential oils known for their attractiveness to fruit flies. The findings indicated that traps using basil extract captured a greater number of fruit flies compared to those with celery extract. Furthermore, varying concentrations of the attractants significantly influenced fruit fly captures. The highest yield of fruit fly captures was observed at a 20% concentration of basil extract. The 20% concentration of basil extract had a higher number of fruit fly captures compared to the 10% and 30% basil extract concentrations, as well as the 10%, 20%, and 30% celery extract concentrations. The study results demonstrated a significant difference in the number of fruit fly captures between basil and celery extracts, with the highest number of captures observed with a 20% concentration of basil extract.